2015
DOI: 10.1097/01.epx.0000471670.64665.8f
|View full text |Cite
|
Sign up to set email alerts
|

Screening for antepartum anxiety and depression and their association with domestic violence among Egyptian pregnant women

Abstract: Symptoms of anxiety and depression were highly reported among this sample of pregnant Egyptian women and were significantly associated with exposure to intimate partner violence. Screening of pregnant women for mental disorders associated with exposure to DV with provision of supportive mental health services, as well as interventions to reduce exposure to DV, should be considered for integration into antenatal care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 29 publications
0
48
4
2
Order By: Relevance
“…A meta-analysis reported that rates of antepartum depression ranged from 15-65% (27), with the current study reporting average results. This was higher than reported results in Egypt where they documented that depression affected 10.4% of participants only while both depression and anxiety were documented in up to 60% of patients (17). This would be rendered to the different tools used for screening for mental disorders and IPV during pregnancy.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…A meta-analysis reported that rates of antepartum depression ranged from 15-65% (27), with the current study reporting average results. This was higher than reported results in Egypt where they documented that depression affected 10.4% of participants only while both depression and anxiety were documented in up to 60% of patients (17). This would be rendered to the different tools used for screening for mental disorders and IPV during pregnancy.…”
Section: Discussioncontrasting
confidence: 61%
“…A previous study evaluated the effect of enabling resources and childhood adverse events on anxiety associated with IPV among Egyptian women (16). In addition, a recent one was conducted to evaluate the association between mental disorders (anxiety and/or depression) with domestic violence (17). Other studies were conducted among non-pregnant women (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdalhai and Mosleh [13] studied antepartum anxiety and depression and their association with domestic violence among Egyptian pregnant women. Their results indicated that, pregnant women who expressed simultaneous anxiety and depressive manifestations accounted for 63%, whereas 11.4% and 10.4% of them expressed only anxiety and only depression.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Due to uctuations and decline in the levels of ovarian hormones, women are at higher risk for mental health issues compared to men (1) and their mental health during reproductive age is a major public health concern in both developing and developed countries (2). There is an association between mental health status and marital satisfaction (3); anxiety and depression are associated with lower marital satisfaction (4,5).…”
Section: Introductionmentioning
confidence: 99%